IMPLEMENTASI SISTEM INFORMASI AKUNTANSI MANAJEMEN UNTUK MENINGKATKAN RESPONSIBILITY ACCOUNTING PADA RSUD LABUANG BAJI SULAWESI SELATAN - Supirman; Ansyarif Khalid; Ismail Badollahi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of Management Accounting Information Systems (MAIS) in enhancing responsibility accounting at the Labuang Baji Regional General Hospital (RSUD), South Sulawesi. The research employs a qualitative approach with a case study design. Data were collected through in-depth interviews with the Hospital Director, Finance Manager, and Finance Staff, supplemented by observation of the accounting system and relevant documents. Data analysis was performed descriptively to identify how MAIS is implemented, what information is generated, and how it is utilized in responsibility accounting practices. The results show that the Hospital Management Information System (SIMRS), as the main MAIS platform, plays a significant role in supporting responsibility accounting. SIMRS successfully integrates operational and financial data from various units in real-time, enabling the identification and tracking of revenues and costs per responsibility center. The system facilitates participatory budgeting, generates automated performance reports comparing actual results with budgets, simplifies variance analysis, and strengthens the accountability of unit heads through a transparent reporting system. Despite these benefits, several challenges were identified, including uneven digital literacy among staff, technical network disruptions, limited managerial understanding of financial responsibility concepts, and a reward and punishment system not yet fully based on objective financial performance data. These findings confirm that SIMRS is a strategic infrastructure supporting the effectiveness of responsibility accounting and fostering a culture of performance and accountability in hospital financial management.